Housing Temperature Modulates the Impact of Diet-Induced Rise in Fat Mass on Adipose Tissue Before and During Pregnancy in Rats - Albustanji, Layla; Perez, Gabriela S.; AlHarethi, Enas; Aldiss, Peter; Bloor, Ian; Barreto-Medeiros, Jairza M.; Budge, Helen; Symonds, Michael E.; Dellschaft, Neele (Frontiers in Physiology, 2019)
Aim: To investigate whether housing temperature influences rat adiposity, and the extent it is modified by diet and/or pregnancy. Housing temperature impacts on brown adipose tissue, that possess a unique uncoupling protein (UCP)1, which, when activated by reduced ambient temperature, enables rapid heat generation. Methods: We, therefore, examined whether the effects of dietary induced rise in fat mass on interscapular brown fat in female rats were dependent on housing temperature, and whether pregnancy further modulates the response. Four week old rats were either maintained at thermoneutrality (27°C) or at a “standard” cool temperature (20°C), and fed either a control or obesogenic (high in fat and sugar) diet until 10 weeks old. They were then either tissue sampled or mated with a male maintained under the same conditions. The remaining dams were tissue sampled at either 10 or 19 days gestation. Results: Diet had the greatest effect on fat mass at thermoneutrality although, by 19 days gestation, fat weight was similar between groups. Prior to mating, the abundance of UCP1 was higher at 20°C, but was similar between groups during pregnancy. UCP1 mRNA followed a similar pattern, with expression declining to a greater extent in the animals maintained at 20°C. Conclusion: Housing temperature has a marked influence on the effect of dietary induced rise in fat deposition that was modified through gestation. This maybe mediated by the reduction in UCP1 with housing at thermoneutrality prior to pregnancy and could subsequently impact on growth and development of the offspring.